Semiautomatic quantification of abdominal wall muscles deformations based on dynamic MRI image registration. (1st February 2021) - Jourdan, Arthur; Le Troter, Arnaud; Daude, Pierre; Rapacchi, Stanislas; Masson, Catherine; Bège, Thierry; Bendahan, David
Abstract : Quantitative analysis of abdominal organs motion and deformation is crucial to better understand biomechanical alterations undermining respiratory, digestive or perineal pathophysiology. In particular, biomechanical characterization of the antero‐lateral abdominal wall is central in the diagnosis of abdominal muscle deficiency. Here, we present a dedicated semiautomatic dynamic MRI postprocessing method enabling the quantification of spatial and temporal deformations of the antero‐lateral abdominal wall muscles. Ten healthy participants were imaged during a controlled breathing session at the L3–L4 disc level using real‐time dynamic MRI at 3 T. A coarse feature‐tracking step allowed the selection of the inhalation cycle of maximum abdominal excursion. Over this image series, the described method combines (1) a supervised 2D+t segmentation procedure of the abdominal wall muscles, (2) the quantification of muscle deformations based on masks registration, and (3) the mapping of deformations within muscle subzones leveraging a dedicated automatic parcellation. The supervised 2D+t segmentation (1) provided an accurate segmentation of the abdominal wall muscles throughout maximum inhalation with a 0.95 ± 0.03 Dice similarity coefficient (DSC) value and a 2.3 ± 0.7 mm Hausdorff distance value while requiring only manual segmentation of 20% of the data. The robustness of the deformation quantification (2) was indicated by high indices of correspondence between the registered source mask and the target mask (0.98 ± 0.01 DSC value and 2.1 ± 1.5 mm Hausdorff distance value). Parcellation (3) enabled the distinction of muscle substructures that are anatomically relevant but could not be distinguished based on image contrast. The present genuine postprocessing method provides a quantitative analytical frame that could be used in further studies for a better understanding of abdominal wall deformations in physiological and pathological situations. Abstract : A novel semiautomatic postprocessing method dedicated to real‐time dynamic MRI aims at fast and reliable quantification of abdominal wall muscle deformations. The described method combines a supervised 2D+t segmentation procedure of the abdominal wall muscles, the quantification of muscle deformations based on masks registration, and the mapping of deformations within muscle subzones leveraging a dedicated automatic parcellation.